Age‐stratified reference intervals unlock the clinical potential of circulating cell‐free DNA as a biomarker of poor outcome for healthy individuals and patients with colorectal cancer - Ørntoft, Mai‐Britt Worm (Int J Cancer, 2020)
Circulating cell‐free DNA (cfDNA) has spurred much interest as a biomarker in oncology. However, inter‐ and intra‐individual cfDNA levels vary greatly. Consequently, in order to base clinical decisions on cfDNA measurements, normal reference intervals are essential to avoid that ordinary variation is confused with clinically relevant change. The lack of reference intervals may potentially explain the ambiguous results reported in the field. Our study aimed to establish reference intervals and to evaluate the association between cfDNA and demographic and clinical variables, including colorectal cancer (CRC). Plasma samples and clinical data from 2817 subjects were collected including 1930 noncancer individuals and 887 CRC patients. cfDNA was measured using droplet digital polymerase chain reaction (PCR). The large cohort combined with robust cfDNA quantification enabled establishment of reference intervals (<67 years: 775‐4860 copies/mL; ≥67 years: 807‐6561 copies/mL). A cfDNA level above the age‐stratified 90% percentile was prognostic of reduced survival in both noncancer individuals and CRC patients, with HR values of 2.56 and 2.01, respectively. Moreover, cfDNA levels increased significantly with age, elevated BMI and chronic diseases. In CRC, the cfDNA level was increased for Stage IV, but not Stage I to Stage III cancer. In summary, the use of reference intervals revealed that high cfDNA levels were predictive of shorter survival in both noncancer individuals and CRC patients, and that CRC development did not affect the cfDNA level until metastatic dissemination. Furthermore, cfDNA levels were impacted by age and chronic diseases. Conclusively, our study presents reference intervals that will help pave the way for clinical utilization of cfDNA.